Hoax narrative construction in the social space of rumbuk randu village in the Mahfud Ikhwan’s novel of Dawuk kisah kelabu dari rumbuk randu (2017) - Rifa Nurafia; Lily Tjahjandari (JOALL (Journal of Applied Linguistics and Literature), 2022)
Hoax becomes a social phenomenon that is formed and formed. This description causes hoaxes to operate in the social space. In the novel Dawuk Kisah Kelabu Dari Rumbuk Randu by Mahfud Ikhwan, hoaxes show that there is a structured effort that leads opinion to provocation. Rural social space becomes a possible field with many differences in capital in society. In this article will explore how hoax strategies in text narratives show rural social spaces that function to defend one's position. This study aims to show social space as a place for hoaxe’s formation. The method used is descriptive analysis method with the theory of Arena Pierre Bourdieu. The findings show that social space is used as a place of defense for a hoax-spreading agent named Warto Kemplung by using provocative language. The social space became the place where Warto Kemplung changed positions to influence the people in the village of Rumbuk Randu. The strategy with the latest topic language and the use of responsive language shows a picture of the production of oral speech as a language capital owned by Warto Kemplung. The existence of Warto Kemplung also shows the existence of village spaces and coffee shops as arenas in society as free fields anyone fill to maintain a position.